2021
DOI: 10.3390/atmos12121560
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Future Climate Change on Runoff in the Amur River Basin Using a Distributed Hydrological Model and CMIP6 GCM Projections

Abstract: The Amur River is one of the top ten longest rivers in the world, and its hydrological response to future climate change has been rarely investigated. In this study, the outputs of four GCMs in the Coupled Model Intercomparison Project Phase 6 (CMIP6) were corrected and downscaled to drive a distributed hydrological model. Then, the spatial variations of runoff changes under the future climate conditions in the Amur River Basin were quantified. The results suggest that runoffs will tend to increase in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…One is to determine the high and low flows by the high and low percentiles based on the flow frequency distribution curve, and is widely used to validate the performance of hydrological models and can reflect the most common situations of high and low flows [32,79]. The other method of description is the annual maximum or minimum of specific moving window mean discharges, and is commonly applied to reflect flood or drought risks [27,80]. Since the changes in future hydrological hazards are focused more in this study, we selected the second method to reflect high and low flows.…”
Section: Statistical Approaches For Analyzing the Changes In High And Low Flowsmentioning
confidence: 99%
“…One is to determine the high and low flows by the high and low percentiles based on the flow frequency distribution curve, and is widely used to validate the performance of hydrological models and can reflect the most common situations of high and low flows [32,79]. The other method of description is the annual maximum or minimum of specific moving window mean discharges, and is commonly applied to reflect flood or drought risks [27,80]. Since the changes in future hydrological hazards are focused more in this study, we selected the second method to reflect high and low flows.…”
Section: Statistical Approaches For Analyzing the Changes In High And Low Flowsmentioning
confidence: 99%
“…The Amur River Basin, spanning Russia, China, and Mongolia, ranks among the ten largest river basins in the world [14]. The Chinese part of the basin constitutes 48% of the entire basin and hosts the majority of freshwater lakes in Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to assess the potential climate change impact on the Jajrood River's flow in the future. For decades, the climate crisis and its negative impacts on the hydrological cycle of watersheds have been studied by scientists around the world [6][7][8][9][10]. Regarding the Tibetan Plateau, which is the highest plateau on earth, Tian et al (2019) [11] reported an increase in temperature, due to the impacts of climate change, on the Lhasa River basin, that will lead to a significant reduction in future flow in the middle of the century (2045-2055) and at the end of the century (2090-2100).…”
Section: Introductionmentioning
confidence: 99%